Teaching health care ethics in physiotherapy education : Proposal for South Africa - H. M. Molatoli (AOSIS, 1999)
This paper presents views of the role of the physiotherapy profession during the Apartheid era in South Africa. It analyses aspects of the Truth and Reconciliation Commission document and finally suggestions are made to prevent similar situations from developing ever again.